The role of nonhuman primate models in the development of cell-based therapies for Parkinson’s disease - Vermilyea, Scott C. (J Neural Transm (Vienna), 2017)
Through the course of over three decades, nonhuman primate (NHP) studies on cell-based therapies (CBTs) for Parkinson’s disease (PD) have provided insight into the feasibility, safety and efficacy of the approach, methods of cell collection and preparation, cell viability, as well as potential brain targets. Today, NHP research continues to be a vital source of information for improving cell grafts and analyzing how the host affects graft survival, integration and function. Overall, this article aims to discuss the role that NHP models of PD have played in CBT development and highlights specific issues that need to be considered to maximize the value of NHP studies for the successful clinical translation of CBTs.